2022
DOI: 10.3390/pharmaceutics14061178
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Downstream Biomarkers to Assess and Optimize Intranasal Delivery of Oxytocin

Abstract: Oxytocin (OT), a mammalian neurohormone associated with social cognition and behavior, can be administered in its synthetic form intranasally (IN) and impact brain chemistry and behavior. IN-OT shows potential as a noninvasive intervention for disorders characterized by social challenges, e.g., autism spectrum disorder (ASD) and anorexia nervosa (AN). To evaluate IN-OT’s efficacy, we must quantify OT uptake, availability, and clearance; thus, we assessed OT levels in urine (uOT) before and after participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…A recent metanalyses has shown that group differences of lower endogenous levels of oxytocin were found specifically in males and younger children [ 56 ]. Recently, we found larger effect sizes and more clearly differentiated pre–post oxytocin level changes after intranasal oxytocin administration when it was measured in urine versus plasma [ 57 ]. Utilizing a two-step cluster (TSC) blinded backward-chaining approach, we were able to identify if individuals belonged to active or placebo groups by changes in their urinary oxytocin measurement alone.…”
Section: Clinical Targets and Utilities Of Oxytocinmentioning
confidence: 99%
“…A recent metanalyses has shown that group differences of lower endogenous levels of oxytocin were found specifically in males and younger children [ 56 ]. Recently, we found larger effect sizes and more clearly differentiated pre–post oxytocin level changes after intranasal oxytocin administration when it was measured in urine versus plasma [ 57 ]. Utilizing a two-step cluster (TSC) blinded backward-chaining approach, we were able to identify if individuals belonged to active or placebo groups by changes in their urinary oxytocin measurement alone.…”
Section: Clinical Targets and Utilities Of Oxytocinmentioning
confidence: 99%